SISTEM SIMBOL DALAM LABUHAN SARANGAN DI KELURAHAN SARANGAN KECAMATAN PLAOSAN KABUPATEN MAGETAN - Sari Ani; Miftahul Huda (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to describe and explain the symbol system contained in the Labuhan Sarangan. This research is a type of qualitative research based on an eclectic approach as an outcome of the collaboration of semiotics and hermeneutics theory. The researcher acts as a human instrument. The data of this research are verbal and nonverbal symbols. Verbal symbol data came from the speeches of the actors in the Labuhan Sarangan. Nonverbal symbol data came from the actions of the actors, equipment, and tools that support the implementation of the Labuhan Sarangan. Data collection was done by observing and interviewing Labuhan Sarangan. Data analysis is done in four stages, namely sorting data according to the range of problems, organizing data in formation and categorization, interpreting data based on empirical understanding, and evaluating data units to produce conclusions. The result of the study showed the findings on the shape, meaning, and function of the symbol. Findings in the form of symbols include verbal and nonverbal symbols. The verbal symbols findings include words or mantras or prayers and gamelan that is used as an accompaniment to the Labuhan Sarangan, which is spoken during the labuhan procession. Findings nonverbal symbols include the actions of the actors, equipment, and tools that support the implementation of the Labuhan Sarangan and the offerings used at the time of the Labuhan Sarangan. The findings on the meaning of symbols include religion, ethics, and philosophy. The function of symbols findings includes the purpose of knowledge, outlook on life, group solidarity, mediation, communication, and participation. Keyword: symbol of offerings, form, meaning, function   Keyword: symbol of offerings, form, meaning, function